Pharmacognostic Evaluation and Standardization of Androsace globifera: Exploring Multifaceted Protocols and Parameters for Herbal Medicine Standardization - ShivShankar, Shweta; Singh, Priyanka; Shukla, Pushpendra Kumar; Singh, Shobha; khare, Ankita (Journal of Neonatal Surgery, 2025)
Androsace globifera contains significant phytochemicals such as saponins and is utilized for treating liver and kidney diseases, amenorrhea, skin allergies, leucorrhoea, and as an abortifacient. Morphological studies reveal that the leaves are diverse in shape, ranging from speculating to elliptical. Organoleptic analysis indicates an astringent taste, aromatic odor, and brittle fracture, with the stem being straight and colored brownish-green. The flowers are pink with 12-15 blooms, five petals, seven sepals, a 1.5 mm style, and a 3 mm capsule. The powdered leaves and roots are greenish and brown, respectively, with an astringent and aromatic odor, and a bitter and acrid taste. Microscopic and physicochemical studies identify vascular bundles and upper and lower epidermal cells. The moisture content of roots and leaves is 2.5% and 3%, respectively. The total ash content of roots and leaves is 25% and 22.5%, acid-insoluble ash is 12.5% and 9%, and water-soluble ash is 10% and 8.9%. The extractive values for roots and leaves are as follows: water (0.8% and 1%), ethanol (4% and 2.25%), chloroform (8% and 8.5%), ethyl acetate (9% and 7%), and methanol (11% and 13%). Leaf constants include a stomatal number of 5, a stomatal index of 2.5-7, a vein islet number of 11-17, a vein termination number of 9-12, and a palisade ratio of 2:6. Fluorescent studies show the leaves and roots as light brown and dark brown, respectively. Histochemical analysis reveals the presence of lignified cellulose and cuticular cell walls, aleurone grains, calcium oxalate, fatty acids, resins, inulin, mucilage, tannins, and hydroxyl anthraquinones.